Hydrodynamic results on multiplicity fluctuations in heavy-ion collisions - Ma, Hong-Hao [UNESP]; Wen, Dan [UNESP]; Lin, Kai; Qian, Wei-Liang [UNESP]; Wang, Bin; Hama, Yogiro; Kodama, Takeshi (Amer Physical Soc, 2020)
Multiplicity fluctuations are one of the most crucial observables in the Beam Energy Scan program of the Relativistic Heavy Ion Collider. It is understood that they can be utilized to probe the whereabouts of the critical point on the phase diagram of the QCD matter. However, a significant portion of these fluctuations is, apart from that related to the QCD phase transition, attributed to the other origins, which we refer to as noncritical ones. The present study is dedicated to the noncritical aspects of the multiplicity fluctuations in heavy-ion collisions. In particular, we focus on those of dynamical origin, such as the hydrodynamic expansion of the system and the event-by-event initial fluctuations, in addition to the usual thermal fluctuations, finite-volume corrections, and resonance decay at the freeze-out surface. The obtained results are compared to those of the hadronic resonance gas model as well as to the experimental data.